Pulmonary high‐resolution ultrashort TE MR imaging: Comparison with thin‐section standard‐ and low‐dose computed tomography for the assessment of pulmonary parenchyma diseases. Issue 2 (30th July 2015) - Ohno, Yoshiharu; Koyama, Hisanobu; Yoshikawa, Takeshi; Seki, Shinichiro; Takenaka, Daisuke; Yui, Masao; Lu, Aiming; Miyazaki, Mitsue; Sugimura, Kazuro
Abstract : Background: To determine the accuracy of pulmonary MR imaging with ultrashort echo time (UTE) for lung and mediastinum assessments using computed tomography (CT) as the reference standard, for various pulmonary parenchyma diseases. Methods: Eight‐five consecutive patients (46 males: mean age, 69 years and 39 females: mean age, 69 years) with various pulmonary parenchyma diseases were examined with chest standard‐ and low‐dose CTs and pulmonary MR imaging with UTE. This was followed by visual assessment using a 5‐point system of the presence of nodules or masses, ground‐glass opacity, micronodules, nodules, patchy shadow or consolidation, emphysema or bullae, bronchiectasis, reticular opacity, and honeycomb and traction bronchiectasis. Presence of aneurysms, pleural or pericardial effusions, pleural thickening or tumor, and lymph adenopathy was also evaluated using a 5‐point system. To compare the capability of the methods for lung parenchyma and mediastinum evaluation, intermethod agreement was evaluated by means of kappa statistics and χ 2 test. Receiver operating characteristic analyses were used to compare diagnostic performance of all methods. Results: Intermethod agreements between pulmonary MR imaging and standard‐dose and low‐dose CT were significant and either substantial or almost perfect (0.67 ≤ κ ≤ 0.98; P  < 0.0001). Areas under the curve for emphysema or bullae, bronchiectasis or traction bronchiectasis and reticular opacity on standard‐dose CT were significantly larger than those on low‐dose CT (emphysema or bullae: P  = 0.0002; reticular opacity: P  < 0.0001) and pulmonary MR imaging (emphysema or bullae: P  < 0.0001; bronchiectasis: P  = 0.008; reticular opacity: P  < 0.0001). Conclusion: Pulmonary MR imaging with UTE is useful for lung and mediastinum assessment and evaluation of radiological findings for patients with various pulmonary parenchyma diseases. J. Magn. Reson. Imaging 2016;43:512–532.